Pharmaceutical standardization and physicochemical characterization of traditional ayurvedic marine drug: incinerated conch shell (shankha bhasma) - Chavan, Sandeep; Tayade, Sonali; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand (Marine Drugs, 2018)
Natural resources such as plants, animals and minerals have always been used by mankind to develop drugs and marine world is no exception. Marine by-products like conches, pearls, mother of pearl shells, corals and so forth have been used by traditional Ayurvedic practitioners for centuries. The unique methods of these preparations are scientifically designed to eliminate unwanted impurities and convert them into bioavailable form. In this study, Conch (Xanchus pyrum) was used as a marine resource of calcium carbonate and was converted pharmaceutically from its aragonite form to calcite. All the steps of preparations and changes in the properties therein were documented and validated. Further, traditional as well as modern analytical tools were used to study its physical and chemical characters to develop a monograph. The physical characterization included particle size, X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Thermogravimetric Analysis (TGA) and Fourier Transform Infra-red (FTIR). Metal composition and heavy metal limits were determined using Inductively Coupled Plasma Optical Emission Spectrometry (ICPOES). This study revealed the rearrangement of aragonite crystals into calcite form by grinding, trituration with aloe vera juice and incineration under controlled conditions. Moreover, the finished product was found to be devoid of organic matrix that is nacre. This study creates a foundation for the development of a master formula for commonly used Shankha Bhasma in Ayurvedic medicines.

Simultaneous identification and estimation of glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid in de‐glycyrrhized Ayurvedic lipid‐based formulation of Glycyrrhiza glabra using dual wavelength reverse phase‐high‐performance liquid chromatography - Kumbhalkar, Bhagyashri; Walunj, Tanhaji; Chavan, Sandeep; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand (Separation Science Plus, 2020)
Plant‐based Ayurvedic formulations such as medicated oils, confectioneries, etc. are developed with a rationale of selecting specific compounds for targeted action and minimal side effects. It is imperative to develop an analytical method to simultaneously identify and quantify the targeted compounds for good resolution with low retention time. The present assay using reverse phase‐high‐performance liquid chromatography is optimized to resolve glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid simultaneously at retention times of 6.6, 8.1, and 10.2 min, respectively, using acidified mobile phase from Glycyrrhiza glabra utilized in Ayurvedic lipid (cow's ghee and sesame oil) based formulations. Raw material, its decoction, and residues formed during preparation steps were extracted in methanol while lipid formulations were extracted using a binary solvent system of methanol and n‐hexane. The separation was performed on Hypersil gold column maintained at 40°C using 0.2% ortho‐phosphoric acid with pH 3.5 in water and acetonitrile as binary gradient mobile phase. The compounds were detected at wavelengths 230 (glabridin) and 254 (glycyrrhizin and 18β‐glycyrrhetinic acid) nm. The method revealed de‐glycyrrhized finished products containing glabridin and 18β‐glycyrrhetinic acid having medicinal value.

Antimicrobial and antioxidant potential of a standardized ayurvedic formulation explains its clinical efficacy as gargles in post-radiotherapy oral cancer patients - Chavan, Sandeep; Bhuvad, Sushama; Kumbhlakar, Bhagyashri; Auti, Jyoti; Walunj, Tanhaji; Pathak, Shridevi; Tanpure, Rahul; Gujar, Shweta; Shinde, Jagdish; Kulkarni, Arvind; Gupta, Vidya; Deshmukh, Vineeta; et al. (Journal of Herbal Medicine, 2021)
Introduction: Exploring the antioxidant and antimicrobial potential of a standardized proprietary poly-herbal powder and evaluating its clinical efficacy as an Ayurvedic gargle (Gandush) for reducing oral microbial load and side effects of radiotherapy in oral cavity cancer patients was the aim of this pilot study. Methods: Formulation (Gandush Churna) comprising Terminalia chebula Retz., Terminalia bellirica (Gaertn.) Roxb., Phyllanthus emblica L. and Curcuma longa L. and its decoction (Gandush Kwath) were standardized. In-vitro antioxidant potential and antimicrobial activity against selective bacterial and fungal strains were studied. Oral cavity cancer patients who had undergone radiotherapy were enrolled. The decoction was prepared by soaking Gandush Churna in water, boiling and reducing by 50 %; and was used for gargling, twice a day, for 7 days. Total microbial count and identification of microbiota in the oral cavity as well as symptoms graded as per Common Terminology Criteria for Adverse Events, were noted before and after the treatment. Change in microbial load and shift in symptom gradations were analyzed. Results: A monograph with physicochemical, chromatography, safety and stability parameters was developed. The decoction possessed good in-vitro antioxidant and antimicrobial activities. Gargling therapy significantly reduced bacterial load while mildly controlled the fungal infection in oral cavity cancer patients. It significantly reduced the severity of symptoms viz. stomatitis and local pain, with considerably decreased xerostomia and dysphagia. Conclusions: Intervention of gargle therapy using poly-herbal formulation may serve as an effective complementary treatment to improve oral hygiene and reduce side effects of radiotherapy in oral cancer patients.
Keywords: Anti-microbial; Antioxidant; Gandush; Gargle therapy; Oral cavity cancers; Radiotherapy side effects